Implementation of Android-Based Application Media in Sharia Stock Investment for Millennial Generation - Hidayati, Amalia Nuril; Warsitasari, Wahyu Dwi (Turast: Jurnal Penelitian dan Pengabdian, 2024)
In the last two years, the millennial generation has been aggressively investing in stocks, including the millennial generation in Trenggalek District. One form of stock investment option is Sharia stocks. Education and training are needed to equip the millennial generation with knowledge about legal and safe Islamic stock investment and skills to use Android-based applications in analyzing financial statements, knowing the JCI (Composite Stock Price Index), and buying and selling shares. For this reason, education and training on investment and the use of android-based application media in Islamic stock investment for millennials in Trenggalek District was conducted with 32 participants aged between 25 and 40 years. Based on the posttest and pretest results, it is known that there is an increase in understanding of Islamic stocks and the ability to invest in Islamic stocks with an increase in score of 24.18%. The results of the pretest and posttest are supported by the results of interviews and observations showing that initially, the participants who did not know at all became more knowledgeable, while those who had learned before gained additional knowledge including in choosing mobile or android applications that can be easily used in investing in Islamic stocks.Dalam dua tahun terakhir, generasi milenial semakin gencar berinvestasi saham termasuk generasi milenial di Kecamatan Trenggalek. Salah satu bentuk pilihan invesatasi saham yaitu saham syariah. Edukasi dan pelatihan dibutuhkan untuk membekali generasi milenial tersebut dengan pengetahuan tentang investasi saham syariah yang legal dan aman serta keterampilan menggunakan aplikasi berbasis android dalam melakukan analisis laporan keuangan, mengetahui IHSG (Indeks Harga Saham Gabungan) dan melakukan jual beli saham. Untuk itu, dilakukan edukasi dan pelatihan tentang investasi dan penggunaan media aplikasi berbasis android dalam investasi saham syariah untuk generasi milenial di Kecamatan Trenggalek dengan peserta pelatihan sebanyak 32 peserta yang berusia antara 25 s.d 40 tahun. Berdasarkan hasil postes dan pretes diketahui bahwa terjadi peningkatan pemahaman tentang saham syariah dan kemampuan investasi saham syariah dengan peningkatan skor sebesar 24.18%. Hasil pretes dan postes tersebut didukung dengan hasil wawancara dan observasi menunjukkan bahwa yang semula peserta sama sekali belum mengetahui menjadi bertambah wawasan, sedangkan yang sudah pernah belajar sebelumnya mendapatkan pengetahuan tambahan termasuk dalam memilih aplikasi mobile atau android yang dapat dengan mudah untuk digunakan dalam melakukan investasi saham syariah.